Bioinspired Photocatalyzed Organic Synthetic Transformations. The Use of Natural Pigments and Vitamins in Photocatalysis - Barata Vallejo, Sebastian (2022)
Due to the necessity for more environmentally benign processes in synthetic organic chemistry, and in particular in photocatalysis, a recourse to photocatalysts that are also found in nature and mimic natural processes to accomplish organic transformations is very appealing. Synthetic useful reactions such as oxidations, reductions, carbon-oxygen, carbon-carbon and carbon-sulfur bond formation reactions, and E-to-Z geometrical isomerization reactions photocatalyzed by biological natural pigments, vitamins, cofactors, and compounds with antiviral activity will be discussed in this account. Interestingly, due to the remarkable redox properties and triplet energies of some of these catalysts that are found in nature, both electron transfer (ET)- and energy transfer (EnT)-driven photocatalytic processes can be accomplished.